2002
DOI: 10.1210/me.2001-0347
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Proteasome-Dependent Degradation of Estrogen Receptor α in ZR-75 Breast Cancer Cells

Abstract: Regulation of estrogen receptor alpha (ERalpha) plays an important role in hormone responsiveness and growth of ER-positive breast cancer cells and tumors. ZR-75 breast cancer cells were grown under conditions of normoxia (21% O(2)) or hypoxia (1% O(2) or cobaltous chloride), and hypoxia significantly increased hypoxia-inducible factor 1alpha protein within 3 h after treatment, whereas ERalpha protein levels were dramatically decreased within 6-12 h, and this response was blocked by the proteasome inhibitor MG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 56 publications
6
68
0
2
Order By: Relevance
“…However, hypoxia did reduce ERa level in cells cultivated in EWD and Tet medium, as well as in cells treated in E 2 medium (Fig. 5C), in accord with the finding of Stoner et al (2002).…”
Section: Dadiani D Seger Et Al: Estrogen Regulation Of Vegf In Brsupporting
confidence: 86%
“…However, hypoxia did reduce ERa level in cells cultivated in EWD and Tet medium, as well as in cells treated in E 2 medium (Fig. 5C), in accord with the finding of Stoner et al (2002).…”
Section: Dadiani D Seger Et Al: Estrogen Regulation Of Vegf In Brsupporting
confidence: 86%
“…3C) and hypoxia-induced inhibition of Ah-responsiveness was observed in cells within 6 hr of growth under hypoxic conditions. Previous studies showed that hypoxia activated proteasomedependent degradation of ERα (Stoner, Saville, Wormke, Dean, Burghardt, and Safe, 2002); however, the proteasome inhibitor MG132 did not reverse the hypoxia-dependent decrease in the induction of CYP1A1 protein by TCDD or the decrease in BRCA1 expression (Fig. 5B).…”
Section: Discussionmentioning
confidence: 72%
“…Hypoxia decreased estrogen-responsiveness in breast cancer cells (Stoner, Saville, Wormke, Dean, Burghardt, and Safe, 2002), and also decreases the magnitude of the antiestrogenic activity of AhR agonists in breast cancer cells (Fig. 1D).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The evidence so far on an association of hypoxia, or factors such as CA9 that are induced by hypoxia, with resistance to endocrine therapy, however, is scarce. Hypoxia has been shown to lead to hormone insensitivity by ER degradation in breast cancer cell lines (Kurebayashi et al, 2001;Stoner et al, 2002). The level of VEGF, which is also induced under hypoxic conditions (Wykoff et al, 2000;Lal et al, 2001), predicts relapse in patients with breast cancer receiving adjuvant endocrine therapy more significantly than after polychemotherapy (Gasparini et al, 1999;Linderholm et al, 2000).…”
Section: Xmentioning
confidence: 99%